PELATIHAN PEMBUATAN TEH HERBAL UNTUK MENINGKATKAN KUALITAS KESEHATAN MASYARAKAT DI DESA CIBIRU WETAN - Istiqomah, Aulia Nurfazri; Roni, Asep; Budiana, Wempi; Lisni, Ida; Zaelani, Diki; Sutrisno, Entris (Jurnal Pengabdian Masyarakat (Jupemas), 2024)
The current condition of Indonesia can be said to be facing a triple burden. Based on research results from the Central Statistics Agency, the percentage of the population, especially the population of West Java, who had health complaints during the last month in 2022 showed an increase compared to the previous year (2021), this is of course related to the quality of public health. The problem currently faced by partners is the lack of information and education regarding the processing of nutritious plants. So far, the crops obtained have been used in simple ways, eaten directly as fresh vegetables or processed as food.This time the community service program was carried out in Cibiru Wetan Village, Cileunyi District, Bandung Regency. Activities include providing education regarding efficacious herbal plants and tutorials on making herbal tea as an effort to improve the quality of health.From the results of implementing this community service activity, the residents of Cibiru Wetan Village, Cileunyi District, Bandung Regency have understood the ingredients that can be used in an effort to improve the quality of health and one way of processing them